Corrosion detection using low-frequency RFID technology - Alamin, M; Tian, G Y; Andrews, A; Jackson, P (Insight (Northampton), 2012)
In this paper we present the novel use of radio frequency identification (RFID) technology as a sensor for corrosion detection. An RFID system consists of two components: the reader and the tag/transponder. The tag is placed on a test sample surface and then measurements are made using the reader coil at a certain height above the tag. The RFID corrosion sensor operates according to the principles of electromagnetic induction. The sample set consists of coated and uncoated mild steel plates, which have rectangular regions that have been exposed to the environment for different durations (1, 3 and 6 months) to create different levels of corrosion. The results show that the RFID corrosion sensor is able to distinguish all the different levels of corrosion. Furthermore, the measurements from the corroded region are consistently different from coating thickness and conductivity/permeability variations across the sample surface.